Leadership : Enhancing the Lessons of Experience - Gordy J. Curphy (McGraw Hill-Education, 2014)
Leadhership development involves reflecting on one's own experiences. Reading this book in the context of your own leadership experience cai aid int that process. The book is comprehensive, scholarly, stimulating, entertaining, and relevant for anyone who wishes to better understand the dynamics of leadership, and to improve her or his own personal performance. The book consists of 4 part. Part one discuss leadership is a process, not a position 1, that consists of 3 chapter. Some materials in this part discuss leadership, leader development and skills for developing yourself as a leader. Part two about focus on the leader. Some material in this part about power and influence, values, ethics, and character, and also about leadership attributes, leadership behavior, and skills for bulding personal credibility and influencing others. Part three discuss about focus on the followers, that consists of motivation, satisfaction, and performance; group, teams, and their leadership, and skills for developing others.